Increased MSME Production through Stimulus Community Partnership Program - Purwantoro, Purwantoro; Rohmah, Rina Ari; Dona, Dona (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This article summarizes the activities of the Stimulus Community Partnership Program implemented in small and medium-sized micro-enterprises. This stimulant community partnership program helps solve the problems faced by partners. The problem is a marketing strategy that is not appropriate for the times, production process, minimal capital, diversification of products that are not updated, and packaging products that are not optimal. The first effort is to increase production through a science and technology approach, and this effort aims to increase production productivity, improve the quality of packaging, improve the quality of a more hygienic work environment. The second effort is to increase marketing through a product diversification approach, and this is done to add product variants of adrem cakes as well as more expensive packaging. The third effort is to change marketing strategy by creating a consumer-preferred taste and a consistent sense, selling on marketplaces and social media, creating brochures/flayers, labeling to look attractive, and other marketing activities.